Integrating Blue Carbon into Indonesia’s Carbon Market Using the Total Economic Value Framework - Marannu Paledung; Nur Hikmah Helida Amahoru; Christy Clayde Latupeirissa (Pattimura Proceeding, 2026)
Blue carbon ecosystems such as mangroves, seagrass meadows, and tidal marshes play a strategic role in climate change mitigation and in the provision of socio-ecological ecosystem services. Indonesia possesses the world’s largest blue carbon potential; however, integrating it into the national carbon market mechanism continues to face conceptual, methodological, and institutional challenges. This article aims to analyze the readiness of Indonesia’s regulatory and institutional frameworks for integrating blue carbon into the carbon market, and to develop an operational framework for applying Total Economic Value (TEV) in blue carbon accounting and valuation. This study adopts a qualitative, document-based approach with structured analysis of national regulations, international guidelines (IPCC, UNFCCC, SEEA-EA, and SEEA-Oceans), sustainability reporting standards (IFRS S2 and GRI), and secondary data derived from official reports and scientific literature. The findings indicate that the main weaknesses lie in limited coastal carbon stock data, the absence of a standardized national baseline, a weak Monitoring, Reporting, and Verification (MRV) system, and the lack of operational integration of TEV into carbon accounting and market mechanisms. This study proposes an integrative framework linking TEV, natural capital accounting, MRV, and sustainability reporting to enhance the credibility, transparency, and economic value of Indonesia’s blue carbon. Policy implications emphasize strengthening blue carbon accounting standards, establishing a national baseline, and cross-institutional integration to support the development of a sustainable carbon market